Prototype Sistem Buka Tutup Pintu Air Otomatis Menggunakan Prakiraan Cuaca - Rizaldi, Fazrin Muhammad; Sujjada, Alun (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Improvements in managing agriculture are urgently needed at this time. Along with the many occurrences of crop failure due to the rainy season which causes flooding in the rice fields. The lack of supervision of the irrigation system makes the water discharge when the rainfall is high, causing the rice plants to be damaged by the flow of water. With this, it is necessary to regulate the immigration channel to prevent crop failure and flooding. Along with this problem, a prototype of an Arduino-based automatic sluice system was made. This prototype has 2 functions, the first is to regulate when the floodgates in the reservoir operate with reference to the water level using an ultrasonic sensor. The sensor signals the Arduino to be processed. The output signal from the Arduino instructs the relay to activate and makes the solenoid work to open or close the water line. The second function is to manage the reservoir which has a water gate leading to the rice field area. This floodgate works with a time setting that can be set as desired. The prototype of the floodgate in irrigation is driven by a 12V DC motor and locks the floodgate when it is opened using a servo motor. With the work of these 2 functions, it can make it easier to regulate the water level in the reservoir and the management of irrigation channels in rice fields.